Modification of CaO from Quail Egg Shells with Sodium Dodecyl Sulfate through Extraction and Precipitation Method as Adsorbent for Methylene Blue Dyes - Widia Purwaningrum; Yolanda Fany Claudia Manurung; Fatma Fatma; Ady Mara (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2024)
Calcium oxide (CaO) is widely used as an adsorbent due to high adsorption effectiveness and can adsorb metals in wastewater and dye waste. The aim of this research is to synthesize CaO from quail egg shells and then modify it using sodium dodecyl sulfate surfactant. Synthesis of CaO was carried out through the extraction method using HCl 1% and precipitation method using Na2CO3 1M. Modified CaO was synthesized by the same method with the addition of Sodium Dodecyl Sulfate (SDS).  Diffractogram peaks on CaO and  CaO modifications are similar to JCPDS data No.88-1811. CaO IR spectrum modification after adsorption showed the addition of functional groups C-N and C=N from methylene blue. CaO and CaO's modifications had pHpzc of 11.82 and 11.62. CaO modification using SDS caused a decrease in the surface area of CaO from 3.9 to 2.5 m2/g and an increase in the pore radius from 3.6 to 13.5 nm. Modification of CaO using SDS decrease the surface area of CaO but adsorption capacity increases 66.19% from 44.63 mg/g to 74.17 mg/g. Kinetic model and adsorption isotherm on CaO and CaO modifications occur in pseudo-second order by following the Langmuir isotherm model. The adsorption process is endothermic and adsorption occurs spontaneously with positive ∆Ho and negative ∆Go values at each adsorption temperature